Respuesta :

Answer:

f(6)=42

Step-by-step explanation:

We know that the equaiton is f(x)=2x+3(x+4). So that means when it is f(6), we plug in 6 into all of the x. Therefore, the equation will be f(6)=2(6)+3(6+4). We combine like terms to get f(6)=12+3(10). We do 3x10 which is equal to 30. f(6)=30+12. 30+12=42. f(6)=42. Therefore, f(6)=42.

If this has helped please mark as brainliest

emmyz

Answer: 47

Step-by-step explanation:

That just means replace the x’s with 6 in the equation. So 2*6+3(6+4)+5. 6+4 is 10, 2*6 is 12. So the equation is now 12+3(10)+5. 3*10 is 30. 12+30+5=47.

ACCESS MORE